Method for preparing modified carbon fiber, marine photovoltaic weather-resistant polyethylene master batch and marine photovoltaic floating body
By performing plasma surface treatment and silane coupling agent treatment on carbon fibers, an "island structure" was formed, which solved the problem of poor compatibility between carbon fibers and polyethylene resins, improved the performance of weather-resistant polyethylene masterbatches for offshore photovoltaics and simplified production process.
Patent Information
- Application Number
- CN202411392950.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively improve the compatibility of carbon fibers and polyethylene resins, resulting in poor performance of weather-resistant polyethylene masterbatches for offshore photovoltaics, and the use of hazardous corrosion reagents by chemical modification method, which is complicated and difficult to industrialize.
The carbon fiber is surface treated by a vacuum plasma cleaning machine to form active groups, and then the filler is adsorbed under the action of silane coupling agent to form a "sea island structure" to improve the compatibility of carbon fibers and polyethylene resin.
It has achieved good compatibility between carbon fiber and polyethylene resin, improved the impact and stress cracking resistance of weather-resistant polyethylene masterbatches for offshore photovoltaics, and simplified the production process and avoided the use of dangerous reagents.
Smart Images

Figure CN119463303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic materials, and in particular to a method for preparing modified carbon fiber, a weather-resistant polyethylene masterbatch for offshore photovoltaics, and an offshore photovoltaic floating body. Background Art
[0002] The sea has abundant sunshine, few obstructions and a large paving area, which has huge potential for photovoltaic power generation. Polyethylene has a regular molecular chain structure and stable chemical properties, low cost and easy acquisition, and is the preferred material for marine photovoltaic buoys. However, the harsher environmental conditions at sea, such as long-term, high-intensity ultraviolet radiation, the impact of irregular waves, etc., limit the application of polyethylene as a marine buoy. Therefore, it is of great significance to develop a polyethylene floating material that is UV-resistant, anti-oxidant, and high-strength and weather-resistant.
[0003] Carbon fiber is mainly composed of carbon elements, and has the characteristics of high temperature resistance, friction resistance, thermal conductivity and corrosion resistance. Therefore, it is often used as a reinforcing agent for the enhancement and modification of polyethylene. However, due to the stability of the molecular structure and the inertness of carbon elements, there are few surface active groups of carbon fibers, which makes it difficult to be compatible with polyethylene and cannot achieve the effect of enhancing performance. Inorganic components including calcium carbonate, hydroxyapatite, talc, carbon black, etc. are often used as fillers for the enhancement and modification of polyethylene. But similarly, due to the phase separation problem, the organic phase and the inorganic phase are usually difficult to be compatible. In addition, the local agglomeration of inorganic fillers is still a limitation of polyethylene processing. The existing technology often modifies carbon fibers by chemical modification to improve compatibility with polyethylene. Dangerous corrosive reagents such as concentrated sulfuric acid and nitric acid are often used in the chemical process, which increases the hazard of production; and the chemical grafting modification operation process is cumbersome and complicated, which reduces production efficiency and is difficult to achieve industrialization.
[0004] Therefore, how to modify carbon fiber to improve the compatibility between carbon fiber and polyethylene resin, and then obtain weather-resistant polyethylene masterbatch with excellent performance for offshore photovoltaics, while avoiding the use of dangerous corrosive reagents and simplifying the operation process is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In response to the above problems, the present invention provides a method for preparing modified carbon fiber, a weather-resistant polyethylene masterbatch for offshore photovoltaics and an offshore photovoltaic float. The purpose is to improve the compatibility with polyethylene resin by modifying the carbon fiber, and then prepare a weather-resistant polyethylene masterbatch for offshore photovoltaics with excellent comprehensive performance.
[0006] In one aspect, the present invention provides a method for preparing modified carbon fiber, comprising the following steps:
[0007] (1) treating the carbon fiber surface with a vacuum plasma cleaning machine to obtain surface activated carbon fiber;
[0008] (2) grinding the filler and filtering through a sieve to obtain filler powder;
[0009] (3) mixing the filler powder obtained in step (2) with a silane coupling agent and a solvent and dispersing the mixture by ultrasonication to obtain an impregnation solution;
[0010] (4) The surface activated carbon fiber obtained in step (1) is subjected to ultrasonic vibration treatment in the impregnation solution obtained in step (3) and then vacuum dried to obtain the modified carbon fiber.
[0011] Optionally, the carbon fiber in step (1) has a diameter of 3 to 10 μm and a length of 2 to 6 mm; and / or
[0012] When performing surface treatment, the gas used in the vacuum plasma cleaning machine is oxygen, the radio frequency is 25-30KHz, the power is 60-80%, the pressure in the cavity is 100-120Pa, and the oxygen flow rate is 3-7cm 3 / min, processing time is 3 to 5min.
[0013] Optionally, the filler in step (2) is one or more selected from talc, carbon black and nano-silicon dioxide, and the sieve is 400-600 mesh; and / or
[0014] The mass ratio of the carbon fiber in step (1) to the talc, carbon black, nano-silicon dioxide in step (2) and the silane coupling agent in step (3) is 100:(0.1-2):(2-8):(1-8):(1-5).
[0015] Optionally, the silane coupling agent in step (3) is silane coupling agent KH550; and / or
[0016] The solvent is anhydrous ethanol.
[0017] Optionally, when preparing the impregnation solution in step (3), the mass ratio of the filler powder, the silane coupling agent and the solvent is (2-6):(0.5-3):(100-150); and / or
[0018] When the ultrasonic oscillation treatment is performed in step (4), the mass ratio of the impregnation liquid to the surface activated carbon fiber is 1 to 2:1; and / or
[0019] The ultrasonic oscillation treatment time is 1 to 2 hours.
[0020] On the other hand, the present invention also provides a weather-resistant polyethylene masterbatch for offshore photovoltaics, comprising the following components in parts by weight:
[0021] Polyethylene resin 100 parts
[0022] Modified carbon fiber 60-75 parts
[0023]
[0024] Wherein, the modified carbon fiber is prepared according to the above method.
[0025] Optionally, the melt mass flow rate of the polyethylene resin is 4.0 to 6.0 g / 10 min, and the density is 0.945 to 0.956 g / cm 3 .
[0026] Optionally, the antioxidant is one or more selected from antioxidant 1010, antioxidant 168 and antioxidant 1076; and / or
[0027] The ultraviolet absorber is one or more selected from UV-327, UV-328 and UV-329.
[0028] Optionally, the light stabilizer is one or more selected from light stabilizer 944, light stabilizer 2020 and light stabilizer 770; and / or
[0029] The dispersant is one or more selected from oxidized polyethylene wax, vinyl bisstearamide and calcium stearate.
[0030] On the other hand, the present invention also provides an offshore photovoltaic floating body, wherein the offshore photovoltaic floating body comprises the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics.
[0031] Beneficial effects:
[0032] (1) When modifying the carbon fiber, the present invention first uses plasma surface treatment technology to form active groups such as hydroxyl and carboxyl groups on the surface of the carbon fiber, and then adsorbs the filler under the action of a silane coupling agent, and part of the filler forms an "island structure" at the fiber interlaced site. At the same time, the alkyl (R) group of the silane coupling agent faces outward, thereby improving the compatibility of the carbon fiber and the polyethylene resin. The intermolecular force between the modified carbon fiber and the polyethylene resin is greater, the bonding is more firm, and the connection strength is greater;
[0033] (2) In the weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention, the "island structure" modified carbon fiber is distributed in the continuous phase polyethylene resin, and the "island structure" formed by the adsorption of fillers can effectively disperse external stress stimulation, thereby improving the impact resistance and environmental stress cracking resistance of polyethylene;
[0034] (3) Compared with other carbon fiber modification technologies such as chemical grafting, the modification method of the present invention is simpler, more convenient, and less time-consuming, thus greatly improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of modified carbon fiber prepared by the method for preparing modified carbon fiber of the present invention;
[0036] Figure 2 is a SEM image of the modified carbon fiber prepared in Example 1 of the present invention;
[0037] Description of Reference Numerals
[0038] 1. Filler; 2. Carbon fiber. DETAILED DESCRIPTION
[0039] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0040] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0041] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0042] In one aspect, the present invention provides a method for preparing modified carbon fiber, comprising the following steps:
[0043] (1) treating the carbon fiber surface with a vacuum plasma cleaning machine to obtain surface activated carbon fiber;
[0044] (2) grinding the filler and filtering through a sieve to obtain filler powder;
[0045] (3) mixing the filler powder obtained in step (2) with a silane coupling agent and a solvent and dispersing the mixture by ultrasonication to obtain an impregnation solution;
[0046] (4) The surface activated carbon fiber obtained in step (1) is subjected to ultrasonic vibration treatment in the impregnation solution obtained in step (3) and then vacuum dried to obtain the modified carbon fiber.
[0047] When modifying the carbon fiber, the present invention first uses plasma surface treatment technology to form active groups such as hydroxyl and carboxyl groups on the surface of the carbon fiber, and then treats the carbon fiber with an impregnation solution formed by mixing a silane coupling agent and a filler (inorganic filler) to modify the surface of the carbon fiber. Since the carbon fiber is first treated with plasma to form more active groups, the surface of the carbon fiber can absorb the filler under the action of the silane coupling agent, and can form a carbon fiber surface such as Figure 1 The "island structure" shown is composed of Figure 1 It can be seen that the carbon fiber 2 forms a fiber network, wherein the "island structure" formed by the filler 1 can be distributed at the sites where the carbon fibers 2 are interlaced with each other. The alkyl (R) group of the silane coupling agent faces outward, becomes oleophilic and hydrophobic, and is easy to mix and connect with the polyethylene resin, improving the disadvantage that the olefin organic phase (polyethylene resin) and the inorganic dispersed phase (carbon fiber) are difficult to combine.
[0048] The present invention adopts plasma surface treatment technology and combines silane coupling agent and filler treatment to prepare "island structure" modified carbon fiber. Compared with other carbon fiber modification technologies such as chemical grafting, the method of the present invention is simpler and more convenient, less time-consuming, greatly improves production efficiency, avoids the use of corrosive reagents, and has better safety.
[0049] In one embodiment of the above method of the present invention, the carbon fiber in step (1) has a diameter of 3 to 10 μm and a length of 2 to 6 mm; and / or
[0050] When performing surface treatment, the gas used in the vacuum plasma cleaning machine is oxygen, the radio frequency is 25-30KHz, the power is 60-80%, the pressure in the cavity is 100-120Pa, and the oxygen flow rate is 3-7cm 3 / min, processing time is 3 to 5min.
[0051] It should be noted that if the length of the carbon fiber is too short, it is impossible to prepare a masterbatch with excellent performance with components such as polyethylene resin. If the length is too long, it is difficult to form when mixed with other components to prepare a masterbatch. Select carbon fiber with the above diameter and length, use oxygen as the plasma treatment gas, and treat it under the above conditions for the above time. At this time, the surface activated carbon fiber obtained in step (1) can be further subjected to steps (2) to (4) to obtain a modified carbon fiber with better surface modification. The modified carbon fiber has better compatibility with polyethylene resin. "Power is 60-80%" means that the power is 60-80% of the rated power of the vacuum plasma cleaning machine (plasma).
[0052] In another embodiment of the above method of the present invention, the filler in step (2) is one or more selected from talc, carbon black and nano-silicon dioxide, and the sieve is 400-600 mesh; and / or
[0053] The mass ratio of the carbon fiber in step (1) to the talc, carbon black, nano-silicon dioxide in step (2) and the silane coupling agent in step (3) is 100:(0.1-2):(2-8):(1-8):(1-5).
[0054] The filler in the "island structure" modified carbon fiber is selected from one or more of talcum powder, carbon black, and nano-silicon dioxide. The filler can be adsorbed on the surface of the high specific surface area carbon fiber after plasma treatment with the characteristics of highly active groups. The modified carbon fiber can be better mixed and connected with the polyethylene resin, solving the incompatibility problem between the traditional inorganic filler and the organic phase, as well as the local agglomeration problem. In this way, the advantages of the modified carbon fiber are fully utilized, and the polyethylene resin is enhanced and modified to improve the mechanical properties.
[0055] In the present invention, the filler can be distributed as a dispersed phase in the continuous phase polyethylene resin, and the modified carbon fiber is used as the main network skeleton to form an "island structure", which has the following advantages:
[0056] First, the polyethylene resin is reinforced and toughened without affecting the overall properties of the polyethylene resin: as a dispersed phase, it also acts as a stress concentration point in the whole. When stimulated by external force, the tip stress of the crack extension will be released by the synergistic effect of the relatively soft modified carbon fiber and the dispersed phase (filler) particles. Therefore, the expansion of the crack is hindered, thereby improving the impact resistance and stress cracking resistance of the polyethylene resin.
[0057] Secondly, in addition to mechanical modification, carbon black and nano-silicon dioxide powder particles also have anti-light aging properties: carbon black is a recognized low-cost and efficient light stabilizer that can effectively absorb destructive radiation energy in ultraviolet rays and capture active free radicals in molecular chains, delaying the aging process of polymers; nano-silicon dioxide has extremely strong ultraviolet absorption and infrared reflection properties. Spectrophotometer tests show that its absorption rate for ultraviolet light within a wavelength of 400nm is as high as 70% or more. The sensitive wavelength of polyethylene resin is generally 300-340nm, indicating that nano-silicon dioxide can be used as a UV absorber to improve the anti-light and oxygen aging properties of polyethylene resin.
[0058] Thirdly, due to the high fluidity and small size effect of carbon black and nano-silica, it is beneficial to the melt processing of polyethylene resin, making the surface of the material denser and cleaner. In addition, the high strength of nanoparticles greatly enhances the strength of polyethylene resin.
[0059] More importantly, when carbon fiber, talcum powder, carbon black, nano-silica and silane coupling agent are compounded in the above ratio, the surface of the carbon fiber can be better modified by talcum powder, carbon black, nano-silica and silane coupling agent, the surface of the modified carbon fiber can be better mixed or compatible with the organic phase polyethylene resin, and the "sea island structure" formed by the fiber interlaced sites can better exert its function to improve the performance of the polyethylene masterbatch formed with components such as the polyethylene resin.
[0060] In one embodiment of the above method of the present invention, the silane coupling agent in step (3) is silane coupling agent KH550; and / or
[0061] The solvent is anhydrous ethanol.
[0062] Silane coupling agents can be used to improve the processability of plastics, improve the interface between inorganic and organic substances, promote the close bonding of modified carbon fibers and polyethylene resins, reduce the viscosity of the resin melt, and improve the dispersion of fillers to improve processing performance, thereby enabling the modified carbon fibers to obtain good surface quality and mechanical, thermal and electrical properties.
[0063] In one embodiment of the above method of the present invention, when preparing the impregnation solution in step (3), the mass ratio of the filler powder, the silane coupling agent and the solvent is (2-6): (0.5-3): (100-150); and / or
[0064] When the ultrasonic oscillation treatment is performed in step (4), the mass ratio of the impregnation liquid to the surface activated carbon fiber is 1 to 2:1; and / or
[0065] The ultrasonic oscillation treatment time is 1 to 2 hours.
[0066] It should be noted that in the method for preparing modified carbon fiber of the present invention, in step (3), the mass ratio of filler powder, silane coupling agent and solvent is controlled as above when preparing the impregnating solution, and in step (4), the mass ratio of the impregnating solution and the surface activated carbon fiber is controlled as above. The surface of the surface activated carbon fiber with more active groups formed by plasma treatment can better adsorb the filler to complete the modification under the action of the silane coupling agent, and form an "island structure" at the fiber interlacing site, which can further improve the compatibility of the carbon fiber with the polyethylene resin.
[0067] On the other hand, the present invention provides a weather-resistant polyethylene masterbatch for offshore photovoltaics, comprising the following components in parts by weight:
[0068]
[0069] The modified carbon fiber is prepared according to the above method.
[0070] The "island structure" modified carbon fiber prepared by the above method of the present invention can be further fused with polyethylene resin under the action of a coupling agent, and as a dispersed network with carbon fiber as the main skeleton, it plays the role of a stress concentration point, that is, when stimulated by external force, the tip stress of the crack extension will be released by the synergistic action of the relatively soft modified carbon fiber and the dispersed phase particles (filler), thereby improving the impact resistance and stress cracking resistance of the resin. The "island structure" increases the surface area of the carbon fiber in contact with the polyethylene resin, further enhances the connection force, and improves the mechanical properties of the polyethylene resin. Therefore, the mechanical properties of the weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention, such as impact resistance and environmental stress cracking resistance, are significantly improved.
[0071] In addition, the present invention utilizes the synergistic effect of multiple antioxidants, light stabilizers and ultraviolet absorbers to greatly improve the anti-oxidation and ultraviolet resistance properties of the weather-resistant polyethylene masterbatch for offshore photovoltaics.
[0072] In one embodiment of the weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention, the melt mass flow rate of the polyethylene resin is 4.0 to 6.0 g / 10 min, and the density is 0.945 to 0.956 g / cm 3 .
[0073] It should be noted that the use of polyethylene resin with a melt mass flow rate and density within the above range can better integrate with the "island structure" modified carbon fiber, and the impact resistance and environmental stress cracking resistance of the weather-resistant polyethylene masterbatch for offshore photovoltaics can be further improved.
[0074] In another embodiment of the weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention, the antioxidant is one or more selected from antioxidant 1010, antioxidant 168 and antioxidant 1076; and / or
[0075] The ultraviolet absorber is one or more selected from UV-327, UV-328 and UV-329.
[0076] It should be noted that antioxidants can delay or inhibit the oxidative aging process of polymers by eliminating the active free radicals produced by the decomposition of polyethylene molecular structures, thereby extending their service life. Ultraviolet absorbers have a strong absorption effect on ultraviolet rays in sunlight (wavelength is 290-460nm), and can absorb and release the destructive energy in the molecular chain in the form of harmless heat energy, avoiding the breakage of the molecular chain and delaying the aging process of the polymer. By selecting one or more of the above-mentioned antioxidants and ultraviolet absorbers, the antioxidant and UV resistance properties of weather-resistant polyethylene masterbatch for offshore photovoltaics can be improved.
[0077] In one embodiment of the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention, the light stabilizer is one or more selected from the group consisting of light stabilizer 944, light stabilizer 2020 and light stabilizer 770; and / or
[0078] The dispersant is one or more selected from oxidized polyethylene wax, vinyl bisstearamide and calcium stearate.
[0079] When part of the ultraviolet rays break through the protective barrier of the ultraviolet absorber and destroy the molecular chain, the molecular chain will produce a large number of active free radicals due to decomposition. At this time, the light stabilizer can quickly capture the free active free radicals in the polymer structure and combine with them, blocking the chain reaction of molecular chain collapse and decomposition, so that the free radicals can no longer continue to damage the molecular chain, thereby delaying the aging of the polymer. The dispersant makes the "island structure" modified carbon fiber loaded with carbon black, talcum powder and nano-silicon dioxide evenly dispersed to avoid entanglement, and has a good lubrication effect.
[0080] Since the easy-breaking wavelength of polyethylene is between 300 and 340 nm, it is very easy to age under strong sunlight due to ultraviolet light (wavelength of 290 to 460 nm) when used in extreme environments such as the sea for a long time. Therefore, ultraviolet absorbers, light stabilizers and antioxidants are further added to the weather-resistant polyethylene masterbatch for offshore photovoltaics of the present invention to play a synergistic role and thus delay the aging process of polyethylene. More importantly, the present invention selects specific ultraviolet absorbers, light stabilizers, antioxidants and dispersants and compound them according to a certain ratio, so that the synergy between multiple components is better, and the performance of the weather-resistant polyethylene masterbatch for offshore photovoltaics is further improved.
[0081] In addition, the present invention can also provide a method for preparing the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics, which comprises:
[0082] The following components in parts by weight are added into a twin-screw extruder for melting, plasticization, extrusion and granulation to obtain the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics:
[0083]
[0084]
[0085] The modified carbon fiber is a modified carbon fiber treated by vacuum plasma, filler and silane coupling agent. The modified carbon fiber is prepared by the method for preparing modified carbon fiber.
[0086] Preferably, the temperature of the twin-screw extruder is 200-230° C., and the aspect ratio of the screw is 30-40.
[0087] On the other hand, the present invention also provides an offshore photovoltaic floating body, which comprises the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics.
[0088] In addition, the above-mentioned weather-resistant polyethylene masterbatch for offshore photovoltaics can also be used for offshore photovoltaic floating platforms.
[0089] The offshore photovoltaic floating body of the present invention is made of weather-resistant polyethylene masterbatch for offshore photovoltaics with excellent performance, so the impact resistance and stress cracking resistance of the offshore photovoltaic floating body of the present invention are significantly improved.
[0090] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0091] In the following embodiments, when a vacuum plasma cleaning machine is used to treat the surface of carbon fiber, the gas used is oxygen, and the manufacturer of the vacuum plasma cleaning machine is FARI, and the model is GD-5;
[0092] The carbon fibers used in the following examples have a diameter of 5.4 μm and a length of 6.0 mm;
[0093] In the following examples, MFR 21.6kg It indicates the melt mass flow rate of polyethylene resin at 190°C and 21.6kg weight;
[0094] The nano-silicon dioxide used in the following examples was purchased from Evonik and has a brand name of AEROSIL 200;
[0095] The oxidized polyethylene wax used in the following examples was purchased from BASF and has a brand number of 62#.
[0096] Example 1
[0097] A method for preparing a weather-resistant polyethylene masterbatch for use in offshore buoys comprises the following steps:
[0098] (I) Preparation of modified carbon fiber
[0099] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 65%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 3min, take out and get it.
[0100] (2) Preparation of filler composite auxiliary powder (filler powder): 1 g of talcum powder, 2 g of carbon black and 2 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and then filtered through a 500-mesh sieve.
[0101] (3) Preparation of "island structure" carbon fiber: the above-mentioned filler composite auxiliary agent powder and 2g of silane coupling agent KH550 are added to 150mL of anhydrous ethanol and dispersed by ultrasonic to obtain a uniformly mixed impregnation solution, and then the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) is ultrasonically shaken in the impregnation solution for 1h, taken out and dried in a vacuum drying oven to obtain the modified carbon fiber.
[0102] (II) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics
[0103] (4) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics: 65 parts of the "island structure" modified carbon fiber obtained in step (3) and 100 parts of polyethylene resin (density 0.952 g / cm 3 , MFR 21.6kg =4.5g / 10min), 6 parts of antioxidant 1010, 10 parts of ultraviolet absorber UV-327, 12 parts of light stabilizer 2020, and 1 part of oxidized polyethylene wax are added into a twin-screw extruder, the screw aspect ratio is 35, the extruder temperature is set to 230°C, and the product can be obtained through melting, plasticizing, extruding, and granulating.
[0104] Example 2
[0105] A method for preparing a weather-resistant polyethylene masterbatch for use in offshore buoys comprises the following steps:
[0106] (I) Preparation of modified carbon fiber
[0107] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 80%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 3min, take out and get it.
[0108] (2) Preparation of filler composite auxiliary powder (filler powder): 0.5 g of talcum powder, 2.5 g of carbon black and 3 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and filtered through a 500-mesh sieve.
[0109] (3) Preparation of "island structure" carbon fiber: the above-mentioned filler composite auxiliary powder and 2.5g of silane coupling agent KH550 are added to 150mL of anhydrous ethanol and dispersed by ultrasonic to obtain a uniformly mixed impregnation solution, and then the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) is ultrasonically shaken in the impregnation solution for 1.5h, taken out and dried in a vacuum drying oven to obtain the modified carbon fiber.
[0110] (II) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics
[0111] (4) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics: 70 parts of the "island structure" modified carbon fiber obtained in step (3) and 100 parts of polyethylene resin (density 0.949 g / cm 3 , MFR 21.6kg =5.6g / 10min), 5 parts of antioxidant 1010 and 2 parts of antioxidant 168, 6 parts of ultraviolet absorbers UV-327, 2 parts of UV-328 and 2 parts of UV-329, 10 parts of light stabilizer 944 and 5 parts of light stabilizer 2020, 1 part of oxidized polyethylene wax, and 0.5 part of calcium stearate are added into a twin-screw extruder with a screw aspect ratio of 35 and the extruder temperature set to 230°C. After melting, plasticizing, extruding, and granulating, the obtained product can be obtained.
[0112] Example 3
[0113] A method for preparing a weather-resistant polyethylene masterbatch for use in offshore buoys comprises the following steps:
[0114] (I) Preparation of modified carbon fiber
[0115] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 70%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 5min, take out and get it.
[0116] (2) Preparation of filler composite auxiliary powder (filler powder): 0.5 g of talcum powder, 3 g of carbon black and 1.5 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and filtered through a 500-mesh sieve.
[0117] (3) Preparation of "island structure" carbon fiber: the above-mentioned filler composite auxiliary agent powder and 1g of silane coupling agent KH550 are added to 150mL of anhydrous ethanol and ultrasonically dispersed to obtain a uniformly mixed impregnation solution, and then the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) is ultrasonically shaken in the impregnation solution for 1h, and then taken out and dried in a vacuum drying oven to obtain the modified carbon fiber.
[0118] (II) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics
[0119] (4) Preparation of weather-resistant polyethylene masterbatch for offshore photovoltaics: 75 parts of the "island structure" modified carbon fiber obtained in step (3) and 100 parts of polyethylene resin (density 0.953 g / cm 3 , MFR 21.6kg=5.1g / 10min), 8 parts of antioxidant 1010, 4 parts of antioxidant 1076, 8 parts of ultraviolet absorber UV-327, 3 parts of UV-328 and 2 parts of UV-329, 8 parts of light stabilizer 2020 and 4 parts of light stabilizer 770, 1.5 parts of oxidized polyethylene wax and 0.5 part of vinyl bisstearamide are added into a twin-screw extruder with a screw aspect ratio of 35 and an extruder temperature of 230°C. After melting, plasticizing, extruding and granulating, the obtained product can be obtained.
[0120] Comparative Example 1
[0121] Polyethylene masterbatch was prepared according to the method in Example 1, except that:
[0122] Without performing steps (1) to (3), the carbon fiber, polyethylene resin, antioxidant, etc. are directly subjected to step (4) to obtain polyethylene masterbatch.
[0123] Comparative Example 2
[0124] Polyethylene masterbatch was prepared according to the method in Example 1, except that:
[0125] Step (1) is not performed, and step (3) is directly performed on the carbon fiber that has not been subjected to vacuum plasma treatment and the filler composite auxiliary powder prepared in step (2).
[0126] Comparative Example 3
[0127] Polyethylene masterbatch was prepared according to the method in Example 1, except that:
[0128] Step (2) is not performed. In step (3), 2 g of silane coupling agent KH550 is added to 150 mL of anhydrous ethanol and dispersed by ultrasonic to obtain a uniformly mixed impregnation solution.
[0129] Test Example 1
[0130] The "island structure" carbon fiber prepared in step (3) of the above Examples 1 to 3 was subjected to scanning electron microscopy analysis, wherein the analysis results of the "island structure" carbon fiber prepared in step (3) of Example 1 are shown in FIG. Figure 2 ,from Figure 2 It can be seen that there are granular substances between the fibers, which are fillers composed of nano-silica, talcum powder and carbon black, which are mixed with carbon fibers to form a similar "island structure", and nano-silica, talcum powder, carbon black and silane coupling agent have completed a good modification of the surface of carbon fibers.
[0131] The weather-resistant polyethylene masterbatch prepared in step (4) of the above Examples 1 to 3 and the polyethylene masterbatch prepared in Comparative Examples 1 to 3 were tested, and the results are shown in Table 1 below:
[0132] Table 1
[0133]
[0134] The weather-resistant polyethylene masterbatch prepared by the invention has better stress cracking resistance, weather resistance, toughness, bending resistance and better mechanical properties.
[0135] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0136] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0137] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements can be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A method for preparing modified carbon fiber, wherein: The steps include: (1) treating the carbon fiber surface with a vacuum plasma cleaning machine to obtain surface activated carbon fiber; (2) grinding the filler and filtering through a sieve to obtain filler powder; (3) mixing the filler powder obtained in step (2) with a silane coupling agent and a solvent and dispersing the mixture by ultrasonication to obtain an impregnation solution; (4) The surface activated carbon fiber obtained in step (1) is subjected to ultrasonic vibration treatment in the impregnation solution obtained in step (3) and then vacuum dried to obtain the modified carbon fiber.
2. The method according to claim 1, wherein: The carbon fiber in step (1) has a diameter of 3 to 10 μm and a length of 2 to 6 mm; and / or When performing surface treatment, the gas used in the vacuum plasma cleaning machine is oxygen, the radio frequency is 25-30KHz, the power is 60-80%, the pressure in the cavity is 100-120Pa, and the oxygen flow rate is 3-7cm 3 / min, processing time is 3 to 5min.
3. The method according to claim 1, wherein: In step (2), the filler is one or more selected from talc, carbon black and nano-silicon dioxide, and the sieve is 400-600 mesh; and / or The mass ratio of the carbon fiber in step (1) to the talc, carbon black, nano-silicon dioxide in step (2) and the silane coupling agent in step (3) is 100:(0.1-2):(2-8):(1-8):(1-5).
4. The method according to claim 1, wherein: The silane coupling agent in step (3) is silane coupling agent KH550; and / or The solvent is anhydrous ethanol.
5. The method according to claim 1, wherein: When preparing the impregnation solution in step (3), the mass ratio of the filler powder, the silane coupling agent and the solvent is (2-6):(0.5-3):(100-150); and / or When the ultrasonic oscillation treatment is performed in step (4), the mass ratio of the impregnation liquid to the surface activated carbon fiber is 1 to 2:1; and / or The ultrasonic oscillation treatment time is 1 to 2 hours.
6. A weather-resistant polyethylene masterbatch for offshore photovoltaics, comprising the following components in parts by weight: in, The modified carbon fiber is prepared according to the method according to any one of claims 1 to 5.
7. The weather-resistant polyethylene masterbatch for offshore photovoltaics according to claim 6, wherein: The melt mass flow rate of the polyethylene resin is 4.0-6.0 g / 10 min, and the density is 0.945-0.956 g / cm 3 .
8. The weather-resistant polyethylene masterbatch for offshore photovoltaics according to claim 6, wherein: The antioxidant is one or more selected from the group consisting of antioxidant 1010, antioxidant 168 and antioxidant 1076; and / or The ultraviolet absorber is one or more selected from UV-327, UV-328 and UV-329.
9. The weather-resistant polyethylene masterbatch for offshore photovoltaics according to claim 6, wherein: The light stabilizer is one or more selected from the group consisting of light stabilizer 944, light stabilizer 2020 and light stabilizer 770; and / or The dispersant is one or more selected from oxidized polyethylene wax, vinyl bisstearamide and calcium stearate.
10. An offshore photovoltaic floating body, wherein: The offshore photovoltaic floating body comprises the weather-resistant polyethylene masterbatch for offshore photovoltaics according to any one of claims 6 to 9.